An Analysis of Second Language Understanding in Young Learners At Public And Islamic Boarding School - Al-Anshory, Moh. Aep Irfan; Riandi, Riandi; Dewi, Kartika (Universitas Mathla'ul Anwar Banten, 2024)
Young learners have the same learning stages in the process, but they will have different results. It is influenced by several factors such as family background or even the learning environment. The purpose of this study was to determine the acquisition of a second language in young students which studying in a different environment in Pandeglang Regency. This research method is descriptive qualitative approach, where the sample is taken from students who study in public schools and Islamic boarding schools. In this study data collection techniques through observation and interviews. In the interview process they were assigned to introduce themselves briefly, and then write it down on paper so that it could be observed to see the results in second language acquisition. Found some differences in the acquisition of a second language, namely English as a result of their learning process in junior high school as a young learner. But in terms of basic things, they can already know and use it.